Perbandingan gaya pengajaran guru Bahasa Melayu dan guru Bahasa Inggeris - Zamri Mahamod; Nik Mohd Rahimi Nik Yusoff; Juliawati Ibrahim (penerbit ukm, 2009)
The study aimed to explore the comparison of profile of teaching styles of language teachers in the Hulu Langat District, Selangor. This study the used survey method. Three hundred Bahasa Melayu and English teachers from five ‘Pusat Kegiatan Guru (PKG)’ were chosen as respondents of the study. The instrument used was a set of questionnaire modified by Grasha Teaching Style. The data was analysed using descriptive and inferential statistics to determine profile distributions and teaching style of the teachers. The result showed that teachers used all the five teaching styles in the Grasha Model. The three teaching styles frequently used were the personal model style that facilitator style and the delegator style. The t-test analysis showed that there were no significant mean differences of teaching stylse based on school session and option. However there were significant differences of the teaching styles based on the subjects taught for the expert style, the formal authority style and the personal model style. The t-test analysis also showed that there was a significant mean difference for teaching styles based on teachers experience for the facilitator style. In conclusion, language teachers used all the five teaching styles which have been adapted to the learning styles of thier pupils.